Association between alcohol consumption and sleep difficulty in a nationwide Korean survey - In Cheol Hwang; Yujin Park; Hong Yup Ahn; Kwan Jung Kim; So-Jung Park (Journal of Research in Medical Sciences)
Background: The data on the association between alcohol intake and sleep quality in a community-based setting are lacking. This study examined overall sleep difficulty according to alcohol habits among Korean adults. Materials and Methods: We analyzed data from 4937 adults who responded to questions about sleep difficulty and drinking habits from the 2019 Korea National Health and Nutrition Examination Survey. Multivariate logistic regression analyses were used to calculate the odds ratios (ORs) and 95% confidence intervals (CIs) for substantial sleep difficulty based on the frequency or amount of alcohol consumption in total and age- and sex-stratified subgroup analyses. Results: Approximately 8.5% of the study population had substantial sleep difficulty. Individuals who drank <1 per week (frequency) or 1–2 cups per time (amount) had the lowest prevalence of substantial sleep difficulty, even compared with nondrinkers. Among drinkers, the association between alcohol use and sleep difficulty was significant in a dose-dependent manner (P for trend: 0.003 in frequency and < 0.001 in amount). Subgroup analysis revealed that significant linear relationships were robust for adults aged <50 years ([ORs] 1.20 [95% CIs 1.03–1.40] for frequency and 1.25 [1.10–1.42] for amount) and females (1.26 [1.10–1.44] for amount). Conclusion: Alcohol consumption is associated with increased sleep difficulties, especially in younger adults and women, underscoring the need for targeted interventions and in-depth research on the effects of alcohol on sleep.